Education and Singing On Earthquake Disaster Emergency Response Skills - Didit Damayanti (International Forum of Researchers and Lecturers, 2025)
Indonesia, based on its geographical location, is a country that is difficult to escape from the threat of natural disasters, one of which is earthquakes. The high number of casualties from natural disasters indicates that the community's emergency response abilities are still very poor, especially among children who lack basic knowledge in disaster management. The purpose of this research is to determine the impact of education and singing to earthquake emergency response abilities among students at MI Rejoagung. This study used a pre-experimental research design with a one-group pretest-posttest approach. The sampling technique resulted in 30 respondents. Data collection was done through interviews and observations, and data analysis used the Paired T-Test. The research findings showed that before the intervention, the majority (57%) of respondents had sufficient abilities with a mean of 10.96. After the intervention, almost all (83%) of the respondents had good abilities with a mean of 24.78. The analysis result yielded a p-value of 0.000 (≤ α 0.05), indicating that there is an influence of education and singing to disaster earthquake response abilities. The education and singing to makes it easier to understand the material and procedures, makes learning more interesting, and is easy to remember. Respondents are advised to continue improving their knowledge and abilities in disaster preparedness through various sources of information and active participation in disaster training or education.